2013
DOI: 10.1103/physrevlett.111.026101
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Friction of a Fluctuating Contact Line

Abstract: We report a direct measurement of the friction coefficient of a fluctuating (and slipping) contact line using a thin vertical glass fiber of diameter d with one end glued onto a cantilever beam and the other end touching a liquid-air interface. By measuring the broadening of the resonant peak of the cantilever system with varying liquid viscosity , we find the friction coefficient of the contact line has a universal form, c ' 0:8d, independent of the liquid-solid contact angle. The obtained scaling law is furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 26 publications
3
54
0
Order By: Relevance
“…They are sold in water solution at a concentration of 4% w/v. A few drops (15)(16)(17)(18)(19)(20) are initially dispersed in 40 ml of poly(vinyl alcohol) (PVA) in deionized water (10-90%). The PVA is purchased from Sigma-Aldrich (product code 363081) and deionized water is produced by a Millipore Milli-Q filtration system, with a resistivity of 18 M cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are sold in water solution at a concentration of 4% w/v. A few drops (15)(16)(17)(18)(19)(20) are initially dispersed in 40 ml of poly(vinyl alcohol) (PVA) in deionized water (10-90%). The PVA is purchased from Sigma-Aldrich (product code 363081) and deionized water is produced by a Millipore Milli-Q filtration system, with a resistivity of 18 M cm.…”
Section: Methodsmentioning
confidence: 99%
“…Our results demand a new theoretical paradigm, beyond hydrodynamics, able to capture the measured dynamics. Considering the relevance of triple-line dynamics on the particle breaching of a fluid interface 16 , we focus our attention on the fluctuations at the triple line during particle diffusion 17 . We suggest that thermally activated deformations of the interface at the triple line drive the system out of mechanical equilibrium and give rise to extra random forces on the particle.…”
mentioning
confidence: 99%
“…Previously, by measuring the broadening of the resonant peak of the hanging fiber cantilever system with varying liquid viscosity p, we found that obeys a scaling law [13],…”
Section: Introductionmentioning
confidence: 98%
“…In a recent experiment [13], we used a newly developed hanging fiber probe [14] based on atomic force microscopy (AFM) to directly measure the friction coefficient of a fluctuating contact line. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small scale of the slip region, the system has only been investigated using molecular dynamics simulations 5,6 and experimental evidence for these theoretical frameworks has been limited, with relatively low spatial resolution 7 or through indirect estimates based on measured forces. 8 In the current manuscript, we present two independent particle tracking velocimetry (PTV) measurements of the fluid velocities close to the substrate and in the near-vicinity of a slowly moving contact line. The first measurement uses conventional flood illumination of the flow field and gives a three-dimensional flow field with a spatial resolution of approximately 1 µm.…”
mentioning
confidence: 99%